(untitled) (Conference Zone, 2023)
It is known that modern high-performance sport is a field of activity in which the athlete’s body is exposed to extreme physical influences, while under conditions of prolonged training and competitive loads, a state of chronic fatigue and recurrent infections can form. If these symptoms do not disappear during the recovery period or during a long rest of the athlete, it is necessary to conduct additional clinical examinations. It is quite difficult to distinguish between physiological fatigue associated with training at the elite level and fatigue of a pathological nature, because such conditions usually reduce the level of performance of the athlete and, as a result, poor performance in competitions.